ANALISIS JARINGAN VLAN UNTUK MENGURANGI CONGESTION & BROADCAST DOMAIN DI JARINGAN LOCAL AREA NETWORK (Studi Kasus : SMK NEGERI TAKERAN) - Ditama, Septian; Winarno, Wing Wahyu; Pramono, Eko (Informasi Interaktif, 2018)
Virtual Local Area Network (VLAN) is a mechanism that can be used to segment network in switch equipment. With the trunking method, the switch can be connected with the router to connect all the VLANs. Through this way existing network equipment can be optimized to support network services.The research is aimed to analyze the current network at SMK Negeri Takeran and optimize the network by proposing changes to the design and use of VLAN. The methodology used in this study is the NDLC method of analysis, design, simulation prototyping, implementation and simulation, monitoring, management.Then the results achieved is to reduce existing problems by building a VLAN network that will reduce the congestion and broadcast domains so as to improve the existing network quality in SMK Negeri Takeran. The conclusion of this research is SMK Negeri Takeran with VLAN able to overcome the problems of congestion and broadcast domain and facilitate network monitoring.Keyword : NDLC, Quality of Service, availability  performance, Delay dan packet loss.